Effect of Culturally Relevant Teaching on Scientific Knowledge among Class VI Students - Ramesh M; M.T.V. Nagaraju (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2025)
India is rich in culture, tradition arts, and ethos. For hundreds of years ago, culturally, economically, linguistically, religiously and ethnically different people living in India and the Indian classroom filled with cultural diversified students commonly called multicultural classroom. It was stated by National Policy on Education (1986), and POA (1992) that need for culture based revision of curriculum. The latest document NEP (2020) recommended that the indigenous knowledge and different cultures needs to be incorporated in the curriculum and textbook; it also suggested that preservation and promotion of Indian culture and ethos must be the high priority. It is very essential to consider students cultural background, language, ethnicity during teaching process. Keeping in view of the importance of culture and its role in learning science, a research study was conducted focused on developing scientific knowledge and skills through Culturally Relevant teaching (CRT). The sample for the present study was 45 students of class VI in Amarkantak, Madhya Pradesh selected purposively. The sample comprises of tribal and non-tribal students. The data was collected with the help of questionnaire and opinionnaire. The collected data was analyzed by t test and frequency percentage. The study findings revealed that the implemented Culturally Relevant Teaching was effective and the students enjoyed learning, also they felt that their culture and language was acknowledged and respected.